ANALISIS PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN CV CAHAYA PENA KARTASURA SUKOHARJO - Sudarwati, Faisal Effendi Putro, Burhanuddin & (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2017)
Increasingly intense business competition resulted in the company faced with thechallenge to maintain viability. CV Cahaya Pena is a company engaged in thepublishing field, located on Jl. Indronoto No. 7, Mangkuyudan, Kartosuro. This studyaims to identify and analyze the effect of compensation and motivation on employeeperformance CV Cahaya Pena partially and simultaneously. This research usesdescriptive quantitative research, a study that serves to describe or provide an overviewof the object under study through a data sample or population numbers. The sample inthis study are employees who worked for the CV Cahaya Pena totaling 42 people. Theanalysis includes the validity, reliability, classic assumption test, multiple linearregression analysis, F test, t test, and the coefficient of determination. Result multiplelinear regression analysis can be written equation Y = 14,438 + 0,144 X1 + 0,539 X2.F Test result, there is a positive and significant effect simultaneously. T test results ofthis study, variable compensation and no significant positive effect on employeeperformance. Meanwhile, motivation variable positive and significant impact onemployee performance. Then proceed with the coefficient of determination, is known by36% Adjusted R square that show donations or contributions of compensation andmotivation together the performance of employees while the remaining 64% iscontributed by other factors, namely labor discipline, leadership, communication, workenvironment, etc. another where researchers did not examine these factors.Keywords: compensation, motivation, employee performance